Distribution Channel Analysis At PT. Sinar Sosro KP Sumedang - Yayat Ginanjar; Ayu Nurjanah (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
PT. Sinar Sosro KP Sumedang is a company engaged in the beverageindustry. However, the distribution varies from year to year and has decreased and increased. The focus of this research is on the channel distribution process carried out at PT. Sinar Sosro KP Sumedang. This studyaims to determine the implementation of the channel, obstacles and efforts to overcome obstacles at PT. Sinar Sosro KP Sumedang. This study uses a descriptive qualitative approach. The sampling technique used purposive sampling technique as many as 3 people, namely Supervisor, Salesman andAssistant Salesman. Data collection techniques include observation,interviews, documentation, and triangulation (combined). The data analysis technique used is the Miles and Huberman model, namely, data reduction, data display, conclusion drawing. The results of this study indicate that the implementation of the distribution channel consists of several stages, namely,product considerations, unit value, perishability of goods, and technicalproperties of the product, and there are obstacles, namely the number of products where the company must be able to take into account the number of products needed by the market required. , because when a company releases a product with the number of opportunities that the market provides,it is afraid that many unsold products will pile up and approach expiration. Forthe PT. Sinar Sosro KP Sumedang further improves distribution channels by expanding market share so that the implementation of marketing or product sales can be high and more.